Resistance components and velocity distributions of open channel flows over bedforms - Fehlman, Henry Michael, author; Shen, H. W., advisor (Colorado State University. Libraries, 1985)
The components of flow resistance and the velocity distributions of open-channel flows over bedforms were investigated by conducting idealized bedform experiments in a laboratory flume. Experiments involving uniform smooth, uniform rough, and nonuniform smooth bedform elements were performed. Local shear stress and pressure on the bedform surface was measured in order to determine the characteristics of skin and form resistance. Total flow resistance was measured directly and compared to the sum of the resistance components. Using the results of this study and published data, relations were developed to enable the prediction of each resistance component. Boundary layer velocity profiles were measured over the bedform surface in the region of reattached flow. An average velocity distribution was developed based on free stream velocity measurements made over the length of the modeled bedform.
Keywords: Channels (Hydraulic engineering)